Ambulatory Bladder Cancer Care in the United States. Issue 3 (May 2019) - Stark, Talia; Shoag, Jonathan E.; Nicolas, Joseph; Patel, Neal; Taylor, Benjamin; Scherr, Douglas S.
Abstract: Introduction: Contemporary data on bladder cancer care in the United States are lacking. We used nationally representative data to characterize outpatient bladder cancer care in the U.S. and identify potential areas for quality improvement. Methods: The NAMCS (National Ambulatory Medical Care Survey), conducted annually by the Centers for Disease Control and Prevention, is designed to generate weighted estimates of national ambulatory care practice patterns. We evaluated NAMCS data from 2001 to 2014 to characterize patient, physician and visit characteristics associated with a diagnosis of bladder cancer. Results: During the 14-year study period there were 7, 410, 240 weighted visits to a urologist for a diagnosis of bladder cancer. The total number of urology visits for bladder cancer significantly increased during the study period (p=0.03). Overall 35% of patients with bladder cancer saw their urologist 6 or more times annually. Mean visit duration was 21.8 minutes. Mean age of patients with a bladder cancer diagnosis was 71.3 years. Men and women accounted for 8, 106, 756 and 3, 052, 690 visits, respectively (p <0.01). Medicare coverage represented the largest payer system (60.7%). Urologists provided smoking cessation counseling to only 21.2% of current smokers and nutrition counseling was provided for just 14.7% of all obese patients with bladder cancer. Conclusions: Bladder cancer visits account for more than half a million ambulatory urology visits annually. Routine lifestyle interventions such as smoking cessation and nutrition counseling should be implemented during urology visits to further improve the care of patients with bladder cancer.